Transformation of personality features and coping strategies depending on the duration of recurrent depressive disorder - Kalenska, Galyna; Maruta, Nataliya; Fedchenko, Viktoriya; Panko, Tamara (Psychosomatic Medicine and General Practice, 2018)
Background. The high prevalence of recurrent depressive disorders and the severity of the medical and social consequences of the depression in the form of chronization, relapse, resistance, disorders of social functioning, quality of life and suicidal behavior place the problem in the rank of the most urgent, requiring study in terms of early diagnosis and assessment of the condition, depending on the duration of the disease. Methods. An integrated approach was used including clinical-psychopathological, psychodiagnostic and statistical methods. 40 patients with recurrent depressive disorders were examined, 35 people without mental disorders were included in the comparison group. Results. The structure of clinical-psychopathological manifestations of the depressive spectrum in patients with the recurrent depressive disorder was characterized by the presence of affective, motivational-will, cognitive, psychomotor and somatic disorders. Among the personality features, patients differed in a more actualization of the non-adaptive copy-strategy and low self-actualization. Conclusion. Data which we received should be considered when conducting diagnostic and psychotherapeutic interventions for patients with the recurrent depressive disorder.